(Up)rooted identities: Caribbean environmental and cultural interplay in Glissant's Mahagony. Issue 1 (2nd January 2016) - Fawaz, Yasmina
ABSTRACT: Three years before the publication of Poétique de la Relation (1990), Mahagony introduces a shift in Glissant's approach to the environment. This novel not only uses the landscape to present the historical and political contexts that were at the forefront of Glissant's earlier work, but it also begins to articulate the tenets of créolisation promoting the rhizomatic and dialectic nature of the environment through the figure of the mahogany tree. Thus, the tree becomes a central figure in the text that allows the reader to navigate the fragmented narrative and interrelated histories of the island and its people. Weaving past, present, and future, Glissant gestures to the environment's didactic capacity by interlocking key concepts of créolisation with the landscape of the novel and the Caribbean island. My reading of the novel explores the ecocritical implications of the novel by establishing the links among the tree, marronnage, and Caribbean culture.